Kunstpädagogische Selbstvergewisserung professionell begleiten - Dreyer, Andrea (Per EduArt. Kunstpädagogische Materialien für Studium und Schule, 2022)
The process of becoming aware of one's own professional self-understanding in art education goes hand in hand with the questioning of subjective theories as well as the critical-reflexive examination of subject-specific, subject-didactic and artistic offers of justification for one's own actions. The non-hierarchical encounter with a multitude of concepts of justification in art teacher education provides a discursive space for the diversity of art pedagogical professionalisation processes in order to enable a continuous reorientation, redefinition and self-presentation.